Anticoagulant peptides derived from animal-sourced traditional Chinese medicine and their pharmacological effects - Ran Liu; Yichen Ding; Xinyan Jiang; Ruijuan Dong; Yuting Zhang; Yutong Hua; Cong Gai; Peng Wei (Elsevier, 2024)
Introduction: Peptide drugs are highly regarded for their therapeutic versatility, safety, and efficacy in treating conditions like cancer, hepatitis, and diabetes. Animal-derived Traditional Chinese Medicines (TCMs) are promising peptide sources, often outperforming plant-based alternatives. The therapeutic effects of leeches, earthworms, and Eupolyphaga sinensis Walkers in thrombosis and blood stasis have been clinically validated, with anticoagulant peptides as key components; however, their pharmacological mechanisms remain unclear. This review categorizes and summarizes anticoagulant peptides from animal-derived TCMs by species. Methods: This study explores the important role of anticoagulant peptides from animal-sourced medicine in treating thrombosis-related diseases. A literature search using keywords like "anticoagulant peptides," "leech peptides," and "earthworm peptides" yielded over 120 articles, of which 85 were selected. Priority was given to studies from the past 20 years, while significant historical research was also noted. Articles lacking specific information on the animal sources of these peptides were excluded. Data were obtained from a diverse range of references, including both ancient and modern texts, the Chinese Pharmacopoeia, Web of Science, PubMed, ScienceDirect, Google Scholar, Springer, and CNKI. Conclusion: This study reviews six promising animal-derived anticoagulant drugs currently in clinical use: leeches, earthworms, scorpions, Eupolyphaga sinensis Walkers, and centipedes. Key peptides under development include hirudin (Hirudo nipponica), WP-30 (Whitmania pigra), Lomburkinase (Eisenia foetida). These peptides exhibit potent anticoagulant, antiplatelet, and anti-inflammatory effects, rendering them valuable in the treatment of cardiovascular diseases, stroke, amenorrhea, cerebral thrombosis, and atherosclerosis. Discussion: This study critically evaluates the therapeutic mechanisms of anticoagulant peptides in animal-sourced medicines, emphasizing the potential of peptide-based therapies across different strains of the same species for traditional Chinese medicine and modern clinical use. Despite promising potential, challenges such as low bioavailability, difficulties in peptide identification, pharmacological evaluation, and toxicity assessment persist. Addressing these issues will facilitate deeper exploration and development of peptide-based therapies.